Enteroparasites in vegetables marketed in an ancient Brazilian city (2017)
Objective To assess contamination by enteroparasites in raw vegetables consumed in the city of São Mateus, Espírito Santo, Brazil.Material and Methods Samples of lettuce (Lactuca sativa) and parsley (Petrosolium sativum) were collected from six popular establishments, such as supermarkets and street markets. The obtained material was analyzed, after washing, by the spontaneous sedimentation method in the Clinical Analysis Laboratory of the Federal University of Espírito Santo, São Mateus Campus.Results From a total of 120 analyzed samples, 71 (59 %) had one or more parasitic contaminants. Lettuce samples had a contamination rate of 78.3 %, and parsley samples of 40 %.Conclusions The results show that the vegetables consumed in the city had protozoa, helminths and arthropods, which points to the need for implementing hygienic-sanitary measures in production, handling and transportation of these vegetables.